Ligand intercellular adhesion molecule 1 has a necessary role in activation of integrin lymphocyte function-associated molecule 1. - Cabañas, C (1993)
The signaling that causes the leukocyte integrin lymphocyte function-associated molecule (LFA-1) to bind firmly to its ligand intercellular adhesion molecule 1 (ICAM-1) is transduced indirectly through other T-cell receptors and is termed inside-out signaling. We show here that the high-affinity state of LFA-1 is characterized by expression of the LFA-1 epitope detected by monoclonal antibody 24. This epitope is expressed not in response to the initial agonist-mediated signal but when LFA-1 binds to ICAM-1, indicating that ligand binding induces an alteration in LFA-1. As would be predicted, the monoclonal antibody 24 epitope is confined to the LFA-1, which is located at the site of contact between T cells and ICAM-1-expressing transfectants. When a fixation protocol for "freezing" receptors is used, only T cells that are fixed after prior exposure to ICAM-1 bind firmly to ICAM-1 a second time. This suggests that, in addition to the inside-out signaling, a previously unrecognized requirement for full activation of the leukocyte integrin LFA-1 is the initial interaction with its ligand ICAM-1. Thus, activation of LFA-1 is in part achieved by an induced fit imposed from without by interaction with ligand.